1953
DOI: 10.1001/archneurpsyc.1953.02320280058006
|View full text |Cite
|
Sign up to set email alerts
|

Study of Adrenocortical Physiology in Normal and Schizophrenic Men

Abstract: In this study the urinary excretion rates of urinary water, total 17-ketosteroids, creatinine, inorganic phosphates, sodium, potassium, uric acid, and corticoids (neutral reducing lipids) were measured ; in addition, in the blood, the lymphocyte and eosinophile count and the sugar content were determined. Methods used in these determinations are cited in references to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1953
1953
1969
1969

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Hoskins (46) suggests that in schizophrenia the adrenal-autonomic mechanism is somehow disturbed, probably ultimately expressing itself in altered metabolism. Work on the adrenals and the emergency functions has been followed up by Hoagland and others (17,39,40,41,42). These studies are typical of the many reported.…”
Section: Eec Studiesmentioning
confidence: 91%
“…Hoskins (46) suggests that in schizophrenia the adrenal-autonomic mechanism is somehow disturbed, probably ultimately expressing itself in altered metabolism. Work on the adrenals and the emergency functions has been followed up by Hoagland and others (17,39,40,41,42). These studies are typical of the many reported.…”
Section: Eec Studiesmentioning
confidence: 91%
“…The relationship of uric acid to schizophrenia is obscure. Hoagland, et al, 22 first found the excretion of uric acid to be significantly higher in schizophrenics in the 40-60 age group. The younger age group, 20-30 years, did not show any difference from th e control group.…”
Section: Discussionmentioning
confidence: 98%
“…The aim was to evaluate the acute changes caused by ECT itself. (2) Series of [10][11] ECTs were performed on two male schizophrenic patients; one, aged 32, with acute recurrence of hallucinations and other symptoms and another, aged 27, in the deteriorated stage of disease. Gonadotropin outputs were examined as often as necessary before, during, and after the treatment periods.…”
Section: Methodsmentioning
confidence: 99%